Response of community‐aggregated plant functional traits along grazing gradients: insights from African semi‐arid grasslands. Issue 3 (15th January 2014) - Moreno García, Cristian A.; Schellberg, Jürgen; Ewert, Frank; Brüser, Katharina; Canales‐Prati, Pablo; Linstädter, Anja; Oomen, Roelof J.; Ruppert, Jan C.; Perelman, Susana B.; Fraser, Lauchlan
Abstract Questions Plant communities fulfil key functions in the ecosystem, which can be characterized by their plant functional traits. In functional ecology, plant communities are considered to hold a set of trait attributes reflecting a specific plant strategy adapted to persist in the environment to which they are exposed. In semi‐arid grasslands of the Republic of South Africa, we addressed the following questions: how are community‐aggregated plant functional traits (CPFT) shaped by grazing gradients; which plant strategies are associated with the response of CPFTs; and are environmental factors, such as soil properties and grazing management, interrelated with the functional response of vegetation to grazing gradients? Location Semi‐arid grasslands close to Thaba Nchu, Free State (Republic of South Africa). Methods Piosphere transects from a water point into the field were established to portray grazing gradients on two communal grazing areas with continuous grazing and two commercial farms with rotational grazing. Along each transect, six plots (5 × 5 m) were evenly distributed. The trait–transect sampling was applied to record 12 CPFT related to light capture and forage quality. A redundancy analysis was performed to derive relationship between CPFTs, grazing gradients and environmental conditions. Results Grazing intensity decreased along piosphere transects, from the water point into the field. Most CPFTs responded to this decreasing gradient of grazing intensity and so allowed derivation of trait syndromes that clearly reflect plant strategies of ruderal and competitive vegetation. Close to water points, plants had higher nitrogen concentrations, fewer cell wall components and higher specific leaf area, hence light capture might be faster and more efficient per leaf area and leaf mass. Plant communities exposed to intensive grazing were well adapted to defoliation, trampling and nutrient accumulation through fast growth rates and a quick return strategy. Conclusions In the sacrifice zone around water points, there is an ecological niche for vegetation communities exhibiting a strategy of fast growth, which is well adapted to intense and frequent grazing and is also associated with forage of high nutritional quality.